2013
DOI: 10.2135/cropsci2012.09.0530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Storage Temperature and Relative Humidity on Viability and Vigor of Treated Soybean Seeds

Abstract: Seed treatments are applied to soybean (Glycine max L. Merrill) seeds to control early season diseases and insects. Unsold, treated soybean seed must be disposed in a different manner than untreated seed. To minimize treated seed disposal costs, it is necessary to improve seed storage. The objective of this study was to determine the best storage environments that would minimize deterioration of chemically treated soybean seed from different maturity groups and seed compositions. Twenty-four soybean varieties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 26 publications
4
43
2
2
Order By: Relevance
“…Thus, in addition to the physiological activities that vary depending on the initial quality of the seed (MBOFUNG et al, 2013), the structure of the substrate, water retention capacity, aeration establishment and temperature also contribute to the increased percentage of germination (MARTINS et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in addition to the physiological activities that vary depending on the initial quality of the seed (MBOFUNG et al, 2013), the structure of the substrate, water retention capacity, aeration establishment and temperature also contribute to the increased percentage of germination (MARTINS et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The optimum moisture content for storing rice seed is between 12-14% (Whitehouse et al, 2015). However, reduction in storage temperature and seed moisture content has been shown to increase seed storage time (Mbofung et al, 2013). Therefore, to achieve acceptable levels of germination and vigour, proper packaging is crucial as inappropriate packaging material leads to deterioration in the quality of seed during storage (Naguib et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This great temperature gradient between the inside and the periphery leads to the creation of ridges in the soft tissue and micro fissures in the cotyledon, and negatively affects the quality of the seed. In addition, as clarified by Mbofung et al (2013) and observed in this study, this kind of situation can increase the susceptibility of the material to latent damages, or even increase its deterioration, thus reducing the longevity and physiological quality of the product itself.…”
Section: Resultsmentioning
confidence: 68%